Clinicopathologic and Radiologic Characteristics of Pleomorphic Lobular Breast Cancer - (:unkn) unknown (My University, 2021)
Objectives: The objective of the study was to evaluate clinicopathologic and radiologic features of patients with pleomorphic lobular breast cancer (pleomorphic lobular carcinoma [PLC]).Methods: We retrospectively evaluated the clinicopathologic and radiologic features of 25 PLC patients treated in ourdivision from 2012 to 2018.Results: Median age was 50 (range, 42–55) and 48% were postmenopausal. The presence of spiculated mass was 92%.Median tumor size was 21.9 mm (SD±12.7 mm) and axillary lymph node positivity was 44%. Frequency of microcalcification was 12% and frequency of occult breast cancer was 8%. About 72% of patients had Stage 2 or 3 disease. Denovo metastatic disease was 8% and another 8% developed metastasis during follow-up. ER, PR, and Her2/neu werepositive in 76%, 44%, and 8%, respectively, and 16% of patients were triple negative. All tumors were Grade III. MedianKi-67 was 22% (range 3–90%). Frequency of lymphovascular invasion was 52%. Patients were followed median of 34.5months (95% CI, 22.2–46.8), since during this period, two patients recurred and five died, median disease-free survivaland overall survival could not be reached.Conclusion: Our data suggest that patients with PLC present with poor prognostic features such as large tumor size,axillary lymph node positivity, and high lymphovascular invasion and tumor grade and Ki-67.